Reduction of vehicle vibration during the transportation of ready-mixed concrete - Kalenov, Ғ.К.; Karbaev, Н.Қ.; Orazaliev, Б.Т.; Sarsenkyzy, А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
This article discusses the research of one of the urgent problems of transportation of binding materials by cars on domestic highways. The study examined the oscillations of cars by disturbing forces, as well as the main sources of disturbances of the oscillations of cars, i.e. road surface bumps; eccentricity, uneven movement and imbalance of the wheels; rotating parts of the engine; transmissions. The idea of ​​the dependence of vehicle vibrations on a road with an uneven surface is traced, while usually experiencing random vibrations. The microprofile of the road is compared as a random function of the length of the road, the distance traveled is taken as the value of X, this tells us that its ordinates at any value of X are a random value. The article clearly explains the statistical characteristics of the random function in relation to the microprofile of the road. It represents the average values, which are different if averaged over the aggregate implementation or for one implementation, i.e. on time.